The impact of gravity waves and cloud nucleation threshold on stratospheric water and tropical tropospheric cloud fraction. Issue 8 (16th August 2016) - Schoeberl, Mark; Dessler, Andrew; Ye, Hao; Wang, Tao; Avery, Melody; Jensen, Eric
Abstract: Using the Modern Era Retrospective‐Analysis for Research and Applications (MERRA) and MERRA‐2 reanalysis winds, temperatures, and anvil cloud ice, we explore the impact of varying the cloud nucleation threshold relative humidity (RH) and high‐frequency gravity waves on stratospheric water vapor (H2 O) and upper tropical tropopause cloud fraction (TCF). Our model results are compared to 2008/2009 winter TCF derived from Cloud‐Aerosol Lidar with Orthogonal Polarization and H2 O observations from the Microwave Limb Sounder (MLS). The RH threshold affects both model H2 O and TCF, while high‐frequency gravity waves mostly impact TCF. Adjusting the nucleation RH and the amplitude of high‐frequency gravity waves allows us to tune the model to observations. Reasonable observational agreement is obtained with a nucleation threshold between 130% and 150% RH consistent with airborne observations. For the MERRA reanalysis, we lower the tropopause temperature by 0.5 K roughly consistent with GPS radio occultation measurements and include 0.1 K high‐frequency gravity wave temperature oscillations in order to match TCF and H2 O observations. For MERRA‐2 we do not need to adjust the tropopause temperature nor add gravity waves, because there are sufficient high‐frequency temperature oscillations already present in the MERRA‐2 reanalysis to reproduce the observed TCF. Key Points: We explore the sensitivity of the stratospheric water vapor (H2 O) to high‐frequency gravity waves and the cloud nucleation threshold Gravity waves have little impact on H2 O, but increase clouds To match observed water vapor and cloud fraction, the global average nucleation threshold relative humidity is between 130 to 150%